2016
DOI: 10.1158/0008-5472.can-16-0481
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Histone Methyltransferases KMT2C and KMT2D Correlates with Improved Outcome in Pancreatic Ductal Adenocarcinoma

Abstract: Genes encoding the histone H3 lysine 4 methyltransferases KMT2C and KMT2D are subject to deletion and mutation in pancreatic ductal adenocarcinoma (PDAC), where these lesions identify a group of patients with a more favorable prognosis. In this study, we demonstrate that low KMT2C and KMT2D expression in biopsies also defines better outcome groups, with median survivals of 15.9 versus 9.2 months (P ¼ 0.029) and 19.9 versus 11.8 months (P ¼ 0.001), respectively. Experiments with eight human pancreatic cell line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 48 publications
0
80
2
Order By: Relevance
“…The precise reason for this in unclear, but might represent a higher propensity for HDR in the pancreatic acinar component compared to the pulmonary epithelium, or a greater ability of the AAV8 serotype used in this study to enable HDR in the mouse genome, independent of exonuclease activity, as was recently shown for certain AAV strains [50]. Finally, our sequencing data showed that while several recurrently mutated PDAC-associated genes, including Smad4 , Gnas , Rnf43 , Kdm6a and Brca2 did not undergo secondary mutations during PDAC development, two genes in particular - Kmt2c ( Mll3 ) and Kmt2d ( Mll4 ), which encode for chromatin regulatory proteins [37] – did demonstrate recurrent alterations. The encoded proteins, Mll3 and Mll4, are histone methyltransferase enzymes that are part of a so-called COMPASS-like complex responsible for addition of methyl residues to lysine residues on histones, which function as an “activation mark”.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The precise reason for this in unclear, but might represent a higher propensity for HDR in the pancreatic acinar component compared to the pulmonary epithelium, or a greater ability of the AAV8 serotype used in this study to enable HDR in the mouse genome, independent of exonuclease activity, as was recently shown for certain AAV strains [50]. Finally, our sequencing data showed that while several recurrently mutated PDAC-associated genes, including Smad4 , Gnas , Rnf43 , Kdm6a and Brca2 did not undergo secondary mutations during PDAC development, two genes in particular - Kmt2c ( Mll3 ) and Kmt2d ( Mll4 ), which encode for chromatin regulatory proteins [37] – did demonstrate recurrent alterations. The encoded proteins, Mll3 and Mll4, are histone methyltransferase enzymes that are part of a so-called COMPASS-like complex responsible for addition of methyl residues to lysine residues on histones, which function as an “activation mark”.…”
Section: Discussionmentioning
confidence: 69%
“…The encoded proteins, Mll3 and Mll4, are histone methyltransferase enzymes that are part of a so-called COMPASS-like complex responsible for addition of methyl residues to lysine residues on histones, which function as an “activation mark”. Loss of function mutations of MLL3 and other COMPASS-like complex proteins is reported in approximately 10% of PDAC, and loss of expression has been associated with better prognosis [37]. We are continuing to explore the relevance of these recurrent non-targeted mutations, including their requirement for tumor formation in the context of other targeted loci using the AAV-CRISPR system.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of KMT2C was associated with attenuated cell proliferation in pancreatic ductal adenocarcinoma and poor outcome in breast cancer [39,40]. Enrichment of H3K4me3 at promoters of stemness genes OCT4, Nanog and Sox2 were reported during erythroblast erythroid differentiation but completely lost at upon erythroid differentiation [41].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, KMT2C-mediated ER signaling is critical for ER-positive breast cancer (25). Current studies indicate that KMT2C mutation may cause loss of function in MAS and other malignancies (26). The high rate of KMT2C mutation and its high rate of SV in chr 7 suggests an important role in MAS.…”
Section: Discussionmentioning
confidence: 98%